2009
DOI: 10.4049/jimmunol.0901340
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1-Dependent Regulation of Myeloid Cell Function in Experimental Autoimmune Uveoretinitis

Abstract: Experimental autoimmune uveoretinitis is an autoimmune disease induced in mice, which involves the infiltration of CD11b+ macrophages and CD4+ T cells into the normally immune-privileged retina. Damage is produced in the target organ following the activation of Th1 and Th17 T cells and by the release of cytotoxic mediators such as NO by activated macrophages. The majority of immune cells infiltrating into the retina are CD11b+ myeloid cells, but, despite the presence of these APCs, relatively limited numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 44 publications
6
48
0
3
Order By: Relevance
“…In support, we observe that tissue damage in experimental retinal inflammation is significantly attenuated when macrophages are removed 21,22 or macrophage/monocyte activation is blocked. 16,[23][24][25] Experimentally, we observe that the tissue is protected when TNF-alpha activity is neutralised (and indeed show the requisite requirement of TNF for macrophage activation in ocular inflammation [26][27][28] ), or by reprogramming macrophage activation threshold with CD200R treatment. These consistent observations have led to a pipeline for therapeutic opportunities to redress activation thresholds of immune cells.…”
Section: Keeping the Peacementioning
confidence: 93%
See 1 more Smart Citation
“…In support, we observe that tissue damage in experimental retinal inflammation is significantly attenuated when macrophages are removed 21,22 or macrophage/monocyte activation is blocked. 16,[23][24][25] Experimentally, we observe that the tissue is protected when TNF-alpha activity is neutralised (and indeed show the requisite requirement of TNF for macrophage activation in ocular inflammation [26][27][28] ), or by reprogramming macrophage activation threshold with CD200R treatment. These consistent observations have led to a pipeline for therapeutic opportunities to redress activation thresholds of immune cells.…”
Section: Keeping the Peacementioning
confidence: 93%
“…43,44 In EAU, both Th1 and Th17 T helper cells are important inducers of autoimmune disease. 35,45 It is the cytokines (especially IFN-γ produced by Th1 cells) produced by these cells that activate the non-specific mononuclear tissue infiltration (principally macrophages) and recruit neutrophils as seen in EAU (eg, through interleukin (IL)-17 produced from Th17 cells 7,8,23,24,[26][27][28] ).…”
Section: Understanding Uveitismentioning
confidence: 99%
“…We have demonstrated that the Mu that accumulate in the target organ modify T cell responses, suppressing T cell proliferation but preserving cytokine secretion. 10 These Mu express cell surface markers such as Gr1 and CD31 that are associated with immune regulation, and to investigate the function of such cells, we generated Mu in vitro from BM cells cultured in an inert environment (hydrophobic PTFEcoated tissue culture bags). We compared the ability of these cells to present antigen with other APCs.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] In this environment, the large majority of CD11b + cells are usually described as macrophages (Mu); they release inflammatory mediators and act as professional antigen-presenting cells (APCs). [8][9][10] They can stimulate autoantigen-specific CD4 + T cells, by presenting MHC class II-restricted peptides and we have recently reported that Mu derived from the inflamed retina of mice with EAU can act as myeloid regulatory cells, inhibiting T-cell proliferation while allowing normal antigenspecific T-cell cytokine production. 10 One important cytokine produced by activated Mu is tumour necrosis factor-a (TNF-a) and the expression of one of its receptors, TNFR1, is necessary for the normal development of organ-specific autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation